(untitled) (The NOUN Journal of Agricultural Research and Development (NJARD), 2025)
70-day feeding trial was carried out to determine the apparent effect of Colocacia esculenta on the growth performance, nutrient digestibility and some carcass traits of turkey poults. Experimental feeds were formulated to meet the dietary/nutritional requirements of the animals. Eighty poults were allocated to five (5) dietary units after brooding for three weeks. Each treatment had a total of sixteen (16) birds with four (4) replicates of four (4) birds per replicate. The experiment was structured in a completely randomized design (CRD). Control treatment (1) had 00% Colocacia esculenta while the rest treatments (2, 3, 4 and 5) had 25, 50, 75 and 100% in that order. The research revealed that some performance traits such as; final weight gain, total weight gain, daily weight gain and daily feed intake were significantly (P<0.05) influenced by the dietary treatments. Total feed intake and feed conversion ratio did not show significant (P>0.05) difference. Results from the digestibility trial depicts that dry matter, crude protein, crude fibre and ether extract were significantly (P<0.05) affected. Dry matter digestibility was better in control treatment and treatment 5 with 100% Colocacia esculenta. Ash and ether extract were not significantly (P>0.05) influenced but showed close statistical values. All the assayed carcass profiles such as bled/slaughter weight, defeathered weight, eviscerated weight and dressing percentage indicated significant (P<0.05) difference. The findings of this research explicitly revealed that Colocacia esculenta meal could replace maize with better performance at 50% level and maintain digestibility and carcass traits of turkey poults.